Synthesis of (−)‐Deoxynupharidine by Allenic Hydroxylamine Cyclisation. Issue 7 (7th May 2015) - Bates, Roderick W.; Lim, Chia Juan; Collier, Steven J.; Sukumaran, Joly
Abstract (−)‐Deoxynupharidine has been synthesised via an intermediate that can also be used for other Nuphar alkaloids. Significant steps include the optimised enzymatic resolution of an allenic alcohol, highly diastereoselective silver‐catalysed cyclisation of an allenic hydroxylamine, selective cross‐metathesis, diastereoselective intramolecular reductive amination, and stereoelectronically controlled enolate alkylation.